The Influence of the Self Assessment System on Compliance Individual Taxpayers in Subang Regency - Ading Rahman Sukmara; Sukmayadi Sukmayadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to examine the effect of the self-assessment system on individual taxpayer compliance. The method used in this research is a quantitative research method. This research uses primary data sourced from KPP Pratama Subang. The sample used was 100 samples, the sample was determined using the slovin formula. Data collection techniques were obtained from observations and questionnaires. Then tested the validity, reliability, classic assumption test, simple regression analysis, and hypothesis testing. The results of the normality test for the two research variables are a significant value of 0.061 > 0.05, so it can be concluded that the residual values ​​are normal distribution. The results of the heteroscedasticity test on the research variables were a significant value of 0.181 > 0.05. The results of a simple regression analysis between the effect of the self-assessment system (X) on the individual taxpayer compliance variable (Y) show that the regression coefficient is 0.349 and the constant value is 52.902. Thus the regression equation obtained is Y = 52.902 + 0.349 X. Where X is the self assessment system and Y is the compliance of individual taxpayers. The test results show that the self-assessment system and Y is individual taxpayer compliance. The test results show that the self-assessment system has an effect on individual taxpayer compliance. From the results of hypothesis testing, the t test produces tcount 4.926 > ttable 1.984. Thus it can be concluded that Ho is rejected, Ha is accepted and the significant value is 0.000, which means it is smaller (<) than 0.05. This means that there is a relationship between the self-assessment system and individual taxpayer compliance.